A re-evaluation of teenage sunbed use following the introduction of banning legislation for under 18-year-olds. (28th February 2019) - Menzies, S; Daly, S; O'Connor, R; Kelly, A; Fitzgerald, M; Bourke, J; McKenna, D B
Abstract: Background: There is little information on the effectiveness of introducing age restriction legislation alone to reduce the rate of sunbed usage by teenagers. Prior to the Public Health (Sunbed) Act of 2014 prohibiting the use of sunbeds in under 18-year-olds in Ireland we reported the rate of sunbed use at 7.5%. Objectives: The aim of the study was to compare the rate of sunbed usage among Irish teenagers before and after the introduction of banning legislation to determine if it had the desired effect of reducing its rate of use. Methods: In a cross-sectional survey, students from the same schools as in our previous study completed an anonymous, written questionnaire pertaining to sunbed usage. Results: In total, 783 questionnaires, from 13 schools across Ireland, were completed. The rate of sunbed use in the current study was 7.2%, compared to 7.5% in the pre-ban study, ( P = 0.76). A higher rate of sunbed use was observed in Dublin schools and female public students. Conclusion: Our study suggests that legislation alone is ineffective at reducing sunbed usage in a teenage population. A multifaceted approach is required that includes enforcement of the legislation together with targeted public education and awareness campaigns using all aspects of the media.